ChemInform Abstract: In situ Formation of β‐Glycosyl Imidinium Triflate from Participating Thioglycosyl Donors: Elaboration to Disarmed—Armed Iterative Glycosylation. Issue 10 (7th March 2013) - Lin, Yu Hsien; Ghosh, Bhaswati; Mong, Kwok‐Kong Tony
Abstract 16 examples for disaccharides, 3 examples for trisaccharides